Professionsforskning som praksisforskning - Buch, Anders (Tidsskrift for Professionsstudier, 2020)
The article investigates the development in the research on professionalism and expertise over the last 50 years and makes suggestions for further development of the research field. Inspired by the ‘turn to practice’ within the social sciences the article sketches a research agenda that may advance the study of professionalism and expertise in promising ways.